Development of Technology-Based Teaching Materials in Islamic Religious Education Subjects - Suharsiwi Suharsiwi; Siti Shofiyah; Fatma Nurmulia; Anis Setiyanti; Rutska Rutska; Paulo Vitor da Silva Santiago (Jurnal al-Thullab, 2024)
This study is motivated by the limited use of interactive and technology-based teaching materials in Islamic Religious Education (PAI), which often relies on conventional lecture methods and results in low student engagement and motivation. The objective of this research is to develop and evaluate the feasibility of technology-based teaching materials in the form of an interactive e-module for junior high school students. The study employs a Research and Development (R&D) method using the Four-D model, consisting of the Define, Design, and Develop stages. Data were collected through expert validation involving lecturers and teachers, as well as student response questionnaires using a Likert scale. The results show that the developed teaching materials are highly feasible, with an average score of 4.65 from both media and material experts, categorized as very appropriate. Student responses also indicate positive perceptions, with an average score of 4.25, reflecting high acceptance and usability. The integration of multimedia elements, such as text, images, videos, and interactive features, enhances student engagement and understanding. This study contributes to the development of innovative, flexible, and student-centered learning resources, supporting independent learning and improving the overall quality of Islamic Religious Education in the digital era.